THE EFFECT OF CAR, NPL AND BOPO ON PROFITABILITY AND STOCK RETURNS IN THE BANKING LISTED ON THE INDONESIA STOCK EXCHANGE IN 2009-2013. - Muhamad, Nahdia Kinanti (FEB Universitas Sam Ratulangi Manado, 2015)
Each investor in stock invesment aims to acquire stock returns. All informations about return and risk of stock investment becomes very important for investors to considered on an investment. Before decide where to invest, investors usually conduct an analysis of the factors that affect stock returns. This research was conducted to examine the effect of CAR, NPL and BOPO on Profitability and Stock returns in the banking listed on the Stock Exchange in 2009-2013. The population used is all banking companies listed on the BEI as many as 41 companies. After used the purposive sampling method, then the sample used is 21 bankings. The analysis technique used in this study is path analysis. The results of this study indicate that CAR and BOPO have significant effect on Profitability, while the NPL has no significant effect, on Profitability. NPL, BOPO and Profitability have a significant effect on Stock Returns while the CAR has no significant effect on Stock Returns. So that the management are should pay attention to the level of efficiency of its operations to improve Profitability and Stock Returns. Keywords: CAR, NPL, BOPO, profitability, stock return.